2013
DOI: 10.3390/s131215880
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of Micro-Beams Considering the Effect of Flexible Supports

Abstract: Normally, the boundaries are assumed to allow small deflections and moments for MEMS beams with flexible supports. The non-ideal boundary conditions have a significant effect on the qualitative dynamical behavior. In this paper, by employing the principle of energy equivalence, rigorous theoretical solutions of the tangential and rotational equivalent stiffness are derived based on the Boussinesq's and Cerruti's displacement equations. The non-dimensional differential partial equation of the motion, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Furthermore, small imperfections, like, e.g., non-zero values of u and θ at no actuation (i.e., for ), could lead to a drift or bias in the solution obtained with the particle filter. It has been also assumed that the beam anchors behave ideally, even if several studies have shown that stress absorption and deformation at the anchors [ 52 , 53 ] can induce an additional compliance and cause discrepancies between the model and measured responses. The effects of these additional sources of uncertainty at the micron or even sub-micron scale will be considered in future investigations.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, small imperfections, like, e.g., non-zero values of u and θ at no actuation (i.e., for ), could lead to a drift or bias in the solution obtained with the particle filter. It has been also assumed that the beam anchors behave ideally, even if several studies have shown that stress absorption and deformation at the anchors [ 52 , 53 ] can induce an additional compliance and cause discrepancies between the model and measured responses. The effects of these additional sources of uncertainty at the micron or even sub-micron scale will be considered in future investigations.…”
Section: Resultsmentioning
confidence: 99%
“…As the surface micromachining process does not allow ideal clamping conditions to be achieved, a torsional stiffnessk e is introduced in the model at the supposed fixed ends. Normally, a complete modelization of the real boundary condition should include a translational spring [29,30] but we assume that the small deflection at the fixed end can be neglected. On the long cantilever, we also add a discrete point mass located at a distancex m from the fixed end in order to consider the mass perturbation.…”
Section: Device Description and Modelmentioning
confidence: 99%
“…Further research of the dynamic effect of nonideal boundary conditions for various types of beams has been reported in Refs. [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…With a lower restoring force at any given deflection, the beam can deflect to a larger amplitude under the same magnitude of electrostatic force. Unlike previous studies on nonideal supports [19][20][21][22][23], which justified dynamic behaviors by modeling the base with springs attached, we purposely added a flexible support to increase vibration amplitudes.…”
Section: Introductionmentioning
confidence: 99%